2018
DOI: 10.1111/jan.13865
|View full text |Cite
|
Sign up to set email alerts
|

Dementia caregiver interventions in Chinese people: A systematic review

Abstract: Aims:The aim of this systematic review was to examine the characteristics and the efficacy of dementia caregiving interventions among the Chinese population.Background: In recent years, an increasing number of dementia caregiving interventions have been developed for Chinese older adults living in Asia that aim to reduce caregivers' burden, depression and distress, and enhance quality of life. Little is known, however, on the nature and the efficacy of these interventions.Design: Systematic review with narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
1
21
0
1
Order By: Relevance
“…74 Consistent with previous meta-analyses conducted in both non-Chinese and Chinese populations, our review showed a general preference of multicomponent interventions in the current literature of dementia caregiving. 29,77,78 It is assumed that multicomponent interventions were more effective than single component interventions. 70,77 However, findings on the effectiveness of multicomponent interventions are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Consistent with previous meta-analyses conducted in both non-Chinese and Chinese populations, our review showed a general preference of multicomponent interventions in the current literature of dementia caregiving. 29,77,78 It is assumed that multicomponent interventions were more effective than single component interventions. 70,77 However, findings on the effectiveness of multicomponent interventions are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…[87][88][89] Implementing interventions at caregivers' homes allowed flexibility for caregivers to use services at any time and stay with their care recipients. 41,78 Paraprofessionals and lay/community health workers have appeared to be effective in promoting health education and service utilization in low-income, underserved, ethnic minorities, as they share similar cultural and linguistic backgrounds of the members and have experiential knowledge of the community. 28,59,67,90 Interventions in Chinese-minority societies also addressed the language barriers to care by providing linguistic adaptations and bilingual services.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies might consider studying the mediating and the moderating effects of positive thinking on care-recipients challenging behavior problems. In fact, the systematic review conducted by Wu and colleagues [49], showed that most of the interventions showed a potential to improve the health and well-being of dementia caregivers and care recipients. In addition, the study conducted by Hughes and colleagues [50], concluded that addressing the potentially modifiable unmet caregiver needs can reduce caregiver burden.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that no articles were published in the top-tier general medical journals, and of the 10 most-cited articles, four articles were randomized controlled trials. Nearly half of the publications related to the health of and intervention for family caregiver of people with dementia were randomized controlled trials, but the review found mixed methodological quality and mixed results in terms of some intervention outcomes [17,18]. Incomplete data reporting, high dropout rates, and recruitment are remaining challenges in study designs in this field [19].…”
Section: Discussionmentioning
confidence: 99%